Virtual boarding school education management: The idea of equitable Islamic education services to the millennial generation - Mursidi, Agus; Kamal, M.; Noviandari, Harwanti; Agustina, Nurul; Nasyafiallah, M. Haddadalwi (Linguistics and Culture Review, 2021)
If general education has been implemented virtually, there is nothing wrong with the same method applied by Islamic education or Islamic boarding schools. For this reason, we will look for data to strengthen this discussion to propose a virtual boarding school education system which is the idea of ??equal distribution of educational services to the millennial generation from house to house. We collect data online on published journals, books, proceedings, and websites that address virtual boarding school education issues. Furthermore, the collected data is analyzed using a coding system, comprehensive evaluation, and drawing conclusions that can answer the main problems of this project. By analyzing and discussing the data, we can conclude that virtual boarding school education is an exciting idea with efforts to distribute Islamic education services to the millennial generation, who happen to be not santri.